A teoria da resolução de problemas aplicada em curso preparatório - Mendes, Carla Gonçalves (2021)
This dissertation aims to analyze the different methods used by students in solving problems that involve basic mathematical knowledge in Elementary School. Therefore, the Problem Solving methodology will be used for interpretation and analysis of collected data. This work makes use of five activities designed by the teacher and applied in the simulation for the Preparatory Course, for the selection test that enables students to entry into High School in Federal and State Technical Schools in the Metropolitan Region of Porto Alegre - RS and Vale do Rio dos Sinos Region - RS in the Mathematics subject. The application of activities through the simulation took place with a group of ten students from the 9th year of Elementary School enrolled in the Preparatory Course of a private institution in the city of Esteio – RS. The carried out research was qualitative and the results presented by the students are shown and analyzed throughout this dissertation.